The impact of limiting long term illness on internal migration in England and Wales: New evidence from census microdata. (October 2016) - Wilding, Sam; Martin, David; Moon, Graham
Abstract: Previous research has suggested that poor health is associated with reduced migration; this knowledge stems from models based on past censuses, or longitudinal studies which imply that the factors influencing migration are the same between those in good and poor health. This paper addresses these issues by utilising health-stratified analyses on the 2011 Census Individual Secure Sample for England and Wales. Multilevel models predict the odds of moving for working age adults, controlling for key predictors of migration, estimating the effect of health status on the odds of moving and the destination-specific variance in migration. We find that those in poor health are less likely to move, after controlling for individual level characteristics. In contrast with expectations, economic inactivity, marriage and being in African, Caribbean, Black, Other or Mixed ethnic groups were not significant predictors of migration among the unhealthy sample, but were for the healthy sample. We conclude that migration is health-selective and propose implications for understanding area level concentrations of poor health in England and Wales. Highlights: This study explores the association between health and internal migration. Using Census microdata for England and Wales. Testing whether the odds of moving vary by area and health status. Several key characteristics not associated with migration for those in poor health. Those in poor health are more likely to move to the Midlands and Eastern England.